Comparative Effectiveness of Dexmedetomidine Versus Esketamine For Pediatric Procedural Sedation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Dewa Putu Agusta Cahya Udayana; I Gusti Ngurah Nyoman Giovani Mahendra Sunantara; Anak Agung Ananda Yudhistira (Riviera Publishing, 2026)
Procedural sedation in children is frequently required but still faces challenges regarding safety and efficacy. Dexmedetomidine (DEX) and esketamine (ESK) are two promising sedative agents for the pediatric population. This systematic review aimed to compare the effectiveness and safety of DEX versus ESK for procedural sedation in children. A systematic search was conducted on PubMed, Cochrane CENTRAL, Embase, Scopus, and Web of Science databases up to May 2026. Inclusion criteria were randomized controlled trials (RCTs) in children aged 0–18 years comparing DEX with ESK. Primary outcomes included sedation success rate, onset time, and recovery time. Secondary outcomes included pain score (FLACC), adverse events, and satisfaction. Heterogeneity was assessed using I² statistics with a random-effects model. Six studies with a total of 654 patients were included. Onset time of DEX was significantly longer than that of ESK (MD = +4.82 minutes; 95% CI: 1.93–7.71; I² = 72%). Sedation success rate showed no significant difference between the two groups (RR = 1.08; 95% CI: 0.94–1.24; I² = 58%). DEX was associated with a higher incidence of bradycardia (RR = 2.34), while ESK was associated with a higher incidence of hypertension/tachycardia (RR = 3.12) and agitation/delirium (RR = 1.89). DEX and ESK have comparable sedation effectiveness in children. ESK provides faster onset, while DEX offers a more stable cardiovascular safety profile with lower risk of psychomimetic effects. Agent selection should be based on the specific clinical needs of the patient and procedure.